Analisis Psikologis Tokoh Utama Dalam Novel “Aku Tak Membenci Hujan’’ Karya Sri Puji Hartini - Rismayanti Rismayanti; Tia Latifah (CV. Aksara Global, 2024)
This article aims to analyze the psychological aspects of the main character in the novel